RANCANG BANGUN ATTACHMENT CYLINDRICAL GRINDING PADA MESIN BUBUT DAN EVALUASI KEKASARAN PERMUKAAN POROS BAJA ST 37 - Muhammad Ikram Kido; Tri Agus Susanto; Haedar Bahri; Sultan Muhammad Shaleh; Ervin Huzaedi (AUSTENIT, 2026)
Conventional lathe machining processes often produce inadequate surface finish quality, which may cause difficulties during component assembly. This study aims to improve the surface roughness (Ra) of ST 37 steel shafts through the design and implementation of a cylindrical grinding attachment mounted on a conventional lathe machine. The research methodology consisted of the design, fabrication, and assembly of the attachment, followed by experimental testing. Grinding experiments were conducted at a constant spindle speed of 1500 rpm with two feed rate variations, namely 0.062 mm/min and 0.079 mm/min. Surface roughness measurements were performed using a surface roughness tester to evaluate the effectiveness of the developed system. The experimental results indicate that a feed rate of 0.062 mm/min produced an average surface roughness of Ra 2.212 μm, whereas a feed rate of 0.079 mm/min resulted in Ra 2.724 μm at the same spindle speed. The findings demonstrate that reducing the feed rate significantly improves surface finish quality. Therefore, the developed cylindrical grinding attachment is effective in enhancing the surface characteristics of ST 37 steel shafts.